STYLISTIC ANALYSIS OF METAPHORS AND SIMILES IN GEORGE ORWELL’S ANIMAL FARM (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This paper investigates the stylistic significance of metaphor and simile in George Orwell’s Animal Farm, a satirical allegory of Soviet totalitarianism. Grounded in theories of cognitive linguistics, particularly those advanced by Lakoff and Johnson (1980), the study highlights how figurative language functions beyond ornamentation to structure thought and intensify political meaning. Through detailed textual analysis, key metaphors and similes are identified and interpreted for their rhetorical, conceptual, and emotional effects. Ultimately, the findings demonstrate that Orwell’s use of figurative language contributes critically to the novel’s aesthetic richness and its ideological critique of oppressive political systems.